PEMILIHAN DAN PENGGUNAAN BAHASA ARAB OLEH MAHASISWA UNIVERSITAS CANAL SUEZ MESIR - Ghita Lusiana Dewi, Muhammad Ridwan (Arabic Literature Department, 2016)
This research aims to describe students preference and the use of Arabic language at the academia, social interactions and media. The data were taken from 24 respondents who are still studying in Suez Canal University in Egypt. The main instrument used in this research named Discourse Completion Test (DCT), in the form of three questionnaires distributed randomly to the selected students as the sample. This research used indirect method with Likert scale to measure the language attitude. The preference and the use of Arabic by students in the field of academic, social interaction, and the media showed a varying result. In field of academic and media, students tend to choose and use BAF, while in the field of social interactions students tend to choose and use BAA.The departments that have the highest percentage on the election and use of the Arabic in the academic are Math, Chemistry, Hospitality, Arabic, and History. Then, in the social interaction field, the percentage of preference and use of BAA by male students is higher than women. These results indicate that departments and gender had a role in the preference and use of the Arabic by students.